If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(-2 + -2g) = 0 (-2 * -6 + -2g * -6) = 0 (12 + 12g) = 0 Solving 12 + 12g = 0 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 12g = 0 + -12 Combine like terms: 12 + -12 = 0 0 + 12g = 0 + -12 12g = 0 + -12 Combine like terms: 0 + -12 = -12 12g = -12 Divide each side by '12'. g = -1 Simplifying g = -1
| 5x+2X-3= | | 4x+y^2=12 | | 2a+4-8a-19= | | -18-6= | | 2(6m+8)= | | 6(10+10g)+2= | | z+(-7)=-5 | | 2ln(x+1)=ln(1-2x) | | .42-1.2=.3r+.6 | | X+11=3x+31 | | 2h=d | | 2(1+8a)+8a= | | 3x-35=125 | | w+6=-9 | | 9m-3m(m+6)=2(m+1) | | -5(-2t+-8)= | | 2.5x-5+8=19.5 | | 0.5n-6=12 | | -1.5x+y=1 | | -1.5+y=1 | | 5(6x-3)=3(8x+1) | | 15x=6y-9 | | -9+7k+8(7+10k)= | | 2(x-2)=x+3 | | y-1.5=1 | | 3x+2x+5=10(x+1) | | 891.25=x(7.5+4.75) | | 22+2s=10+5s | | 22+2s=1 | | -12=-2h+4-1.2h | | 3x-5x+6=12 | | 2(2x-14)=x+2 |